Higher Education Branding In Private University In Electronic Word-Of-Mouth At Medan City - Annisha Suvero Suyar; Tapi Rondang Ni Bulan (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
This study aims to determine the effect of brand understanding, brand influence and brand credibility on the selection of private universities in electronic word of mouth, either partially or simultaneously. The population in this study was 100 with a sample of 100 respondents using a sampling technique, namely probability sampling. The analysis technique used is multiple linear regression. The results showed that brand understanding had no effect on the selection of private universities in electronic word of mouth, brand influence had no effect on the selection of private universities in electronic word of mouth, brand credibility had a positive and significant effect on the selection of private universities in electronic word of mouth. , brand understanding, brand influence and brand credibility have a positive and significant effect on the selection of private universities in electronic word of mouth and the selection of private universities in electronic word of mouth (y) is influenced by X1 (brand understanding), X2 (brand influence), and X3 (brand credibility) of 10.7% Abstract This study aims to determine the effect of brand understanding, brand influence and brand credibility on the selection of private universities in electronic word of mouth, either partially or simultaneously. The population in this study was 100 with a sample of 100 respondents using a sampling technique, namely probability sampling. The analysis technique used is multiple linear regression. The results showed that brand understanding had no effect on the selection of private universities in electronic word of mouth, brand influence had no effect on the selection of private universities in electronic word of mouth, brand credibility had a positive and significant effect on the selection of private universities in electronic word of mouth. , brand understanding, brand influence and brand credibility have a positive and significant effect on the selection of private universities in electronic word of mouth and the selection of private universities in electronic word of mouth (y) is influenced by X1 (brand understanding), X2 (brand influence), and X3 (brand credibility) of 10.7% Keywords: Brand Understanding, Brand Influence, Brand Credibility, Pemilihan Perguruan Tinggi Swasta Dalam Electronic Word Of Mouth